Analisis Penerapan Prinsip-Prinsip ISO 26000 dalam Sustainability Reporting pada Perusahaan Manufaktur: Studi Kasus pada PT. Campina Ice Cream Industry Tbk (Lembaga Pengembangan Kinerja Dosen, 2025)
Awareness of the importance of sustainability has driven many companies to prepare reports that reflect their commitment to social responsibility. This study aims to evaluate the extent to which the principles of ISO 26000 are implemented in the sustainability report of PT Campina Ice Cream Industry Tbk. The research method used is descriptive qualitative, with data sourced from the 2024 annual and sustainability reports. The analysis results show that the company has adopted seven core principles of ISO 26000 transparency, accountability, ethical behavior, and respect for human rights reflected in the company’s policies, CSR programs, and reporting that follows GRI guidelines and OJK regulations. The implementation of these principles has led to improved reporting quality, strengthened stakeholder trust, and demonstrated the company’s commitment to sustainability. However, the limitation of this study is the absence of primary data collection, such as field observations or direct interviews. Therefore, the findings should be interpreted cautiously, and the study is expected to serve as a practical reference for other companies in preparing more structured sustainability reports and expanding academic understanding of ISO 26000 implementation in the manufacturing industry.